Selective inactivation of hypomethylating agents by SAMHD1 provides a rationale for therapeutic stratification in AML - Oellerich, Thomas; Schneider, Constanze; Thomas, Dominique; Knecht, Kirsten M.; Buzovetsky, Olga; Kaderali, Lars; Schliemann, Christoph; Bohnenberger, Hanibal; Angenendt, Linus; Hartmann, Wolfgang; Wardelmann, Eva; Rothenburger, Tamara; et al. (Nature communications, 2019)
Hypomethylating agents decitabine and azacytidine are regarded as interchangeable in the treatment of acute myeloid leukemia (AML). However, their mechanisms of action remain incompletely understood, and predictive biomarkers for HMA efficacy are lacking. Here, we show that the bioactive metabolite decitabine triphosphate, but not azacytidine triphosphate, functions as activator and substrate of the triphosphohydrolase SAMHD1 and is subject to SAMHD1-mediated inactivation. Retrospective immunohistochemical analysis of bone marrow specimens from AML patients at diagnosis revealed that SAMHD1 expression in leukemic cells inversely correlates with clinical response to decitabine, but not to azacytidine. SAMHD1 ablation increases the antileukemic activity of decitabine in AML cell lines, primary leukemic blasts, and xenograft models. AML cells acquire resistance to decitabine partly by SAMHD1 up-regulation. Together, our data suggest that SAMHD1 is a biomarker for the stratified use of hypomethylating agents in AML patients and a potential target for the treatment of decitabine-resistant leukemia. In acute myeloid leukemia, hypomethylating agents decitabine and azacytidine are used interchangeably. Here, the authors show that the major metabolite of decitabine, but not azacytidine, is subject to SAMHD1 inactivation, highlighting SAMHD1 as a potential biomarker and therapeutic target